Examining Compulsive Sexual Behavior and Psychopathology Among a Sample of Postdeployment U.S. Male and Female Military Veterans. Issue 2 (6th February 2017) - Kraus, Shane W.; Martino, Steve; Potenza, Marc N.; Park, Crystal; Merrel, Jeremy D.; Hoff, Rani A.
Abstract : Compulsive sexual behavior (CSB) is defined as difficulties in controlling inappropriate or excessive sexual fantasies, urges, or behaviors that cause subjective distress or impairment in important areas of daily functioning. Using data from a baseline telephone interview, we examined the prevalence of CSB in a convenience sample of 820 postdeployed U.S. military male and female veterans and investigated correlates of CSB with sociodemographics and other mental health and sexual history characteristics. More men (13.8%) than women (4.3%) endorsed CSB-related symptoms. Given the limited sample size of women reporting CSB, correlational analyses were conducted only with men. After adjusting for significant sociodemographics, results indicated that gambling, suicidality, and sexually transmitted infections were significantly associated with male CSB. Current results suggest that CSB may be prevalent among U.S. military veterans post deployment and associated with significant negative health indices in men. CSB warrants attention regarding screening and intervention.